Anaerobic Brain Abscess following Chronic Suppurative Otitis Media in a Child from Uganda - KA Cox; G Al-Rawahi; TR Kollmann (Canadian Journal of Infectious Diseases and Medical Microbiology)
Brain abscess, while rare, confers high mortality, especially in the developing world. The case of a Ugandan child with a polymicrobial brain abscess including infection with Tissierella praeacuta/Clostridium hastiforme requiring repeated drainage and eventual surgical excision is reported. The case demonstrates the importance of considering anaerobic organisms in the treatment of children with brain abscess from the developing world.